The Clinical and Pathological Features of Children With Microscopic Polyangiitis - Li, Qian; Yu, Li-Chun; Li, Feng-Xia; Wang, Jing; Chen, Yuan; Sun, Shu-Zhen (Frontiers in Pediatrics, 2021)
Objective: The aim of this study was to explore the clinical features, pathological characteristics, and the prognosis of children with microscopic polyangiitis (MPA)．Methods: Ten children with MPA that were hospitalized in our hospital were included in this study. The children’s pre-diagnosis status, clinical manifestations, renal pathology, treatment, and prognosis data were analyzed retrospectively. Results: All 10 cases included female patients with a median age of 8.9 years old at the time of diagnosis. MPO-ANCA antibody was positive in all cases, combined with a positive anti-GBM antibody in 2 cases. Nine cases had primary AAV and 1 had antithyroid drug (ATD)-associated MPA (secondary to methimazole). Renal involvement was found in all 10 patients, lung impairment was present in 8 cases, and anemia was present in 9 patients. Renal biopsies were performed in all 10 patients. Segmental focal or global glomerular necrosis was observed in 70% of the patients (7/10). The treatment mainly included steroid use combined with Cyclophosphamide and Mycophenolate. The follow-up s of the patients revealed normal renal function in 8 patients and progression to end-stage renal disease (ESRD) in 2 patients. Conclusions: Female predisposition and positive MPO-ANCA antibody were prominent in children with MPA. The patients’ kidneys and lungs were the most frequently involved organs. Corticosteroid combined with immunosuppressive therapy was recommended for the treatment of MPA. Early diagnosis, prompt aggressive treatment, and regular follow-ups are also very important factors associated with a good prognosis.